KONSTRUKSI PEMBERITAAN PERNIKAHAN BEDA AGAMA - Dionni Ditya Perdana; Wahyu Widiastuti (UNIVED PRESS, Universitas Dehasen Bengkulu, 2020)
Indonesia is a country that has diversity of ethnicities, races, religions and cultures. The issue of SARA is a sensitive matter for someone, especially related to belief (religion). Even though it is in the private sphere, in fact the media's attention is quite sharp on religious issues, one of which is interfaith marriage. Celebrities become figures whose private life becomes a commodity in the mass media. Therefore, this study wants to know the construction of mass media coverage in Indonesia on cases of marriage with different religions. The research was conducted by observing online media, documentation, and literature review. The results showed that the media still often take sensational aspects such as debates in the family and controversial views of society. The media is less sensitive to the issue of religious pluralism in Indonesia. The construction of media on the choice of reality is important to build pluralism in Indonesia with the existing diversity of religions. In creating awareness of pluralism in society, it is necessary to take part in the media to construct news where the media need to highlight the side of peace among religious communities rather than debate.